Study of Kinetic Modelling of Syngas Production Over Plasma Gasification - ., Supriyanto; ., . (International Journal of Engineering and Technology, 2018)
Plasma gasification is able to produce syngas from several feedstock e.g. sawdust, pellet, plastic and oil but there is lack of knowledge in this process through kinetic modelling. To have better understanding this study determines parameters kinetic modelling due to changes of temperature and conversion. The method uses the stoichiometry chemical reaction, material balance, energy balance, and numerical solutionÂ Â to calculate parameters of kinetic modelling. The result of simulation gets pre-exponential factor 9.78 to 13.1 for sawdust, pellet, and plastic with temperature 1200-1500oC and conversion 99%. Meanwhile oil need a higher temperature 1600oC to achieve similar conversion and it indicate a higher pre-exponential factor 67.6 than other feedstock.Â